Вуглепластик конструкційного призначення на основі ароматичного поліаміду і метал-вмісного вуглецевого волокна - Чигвінцева, Ольга Павлівна; Chigvinteva, Olha; Рула, Ірина Василівна; Rula, Irina (Луцький національний технічний університет, 2021)
Досліджені основні теплофізичні і фізико-механічні характеристики ароматичного поліаміду фенілон С-2, армованого метал-вмісним вуглецевим волокном. Показано, що армування поліамідного в’яжучого хром-вмісним вуглецевим волокном у кількості 17 мас. % суттєво знижує питому теплоємність і температурний коефіцієнт лінійного розширення, а також покращує його фізико-механічні властивості. The main thermophysical and physico-mechanical characteristics of the aromatic polyamide phenylon C-2, reinforced with a metal-containing carbon fiber, have been investigated. It is shown that the reinforcement of the polyamide binder with chromium-containing carbon fiber in an amount of 17 wt. % significantly reduces the specific heat and the temperature coefficient of linear expansion, and also improves its physical and mechanical properties. It was found that the developed carbon fiber reinforced plastic has an average of 20-60% and 6-12 % lower, respectively, in comparison with the binder, the temperature coefficient of linear expansion and specific heat. Reinforcement of a polyamide binder with a carbon fiber filler increases its yield point and modulus of elasticity in compression by 20 and 124 MPa, respectively.
Сarbon construction purpose based on aromatic polyamide and metal-containing carbon fiber
Keywords: ароматичний поліамід фенілон С-2; aromatic polyamide phenylone С-2; хром-вмісне вуглецеве волокно; chromium-containing carbon fiber; вуглепластик; carbon plastic; питома теплоємність; specific heat; температурний коефіцієнт лінійного розширення; temperature coefficient of linear expansion; фізико-механічні властивості; physico-mechanical properties